Season-1, Episode 2- of 'Participatory Action Research Feminist trailblazers and good Troublemakers' (Guest- Renu Kha - (:unkn) unknown (My University, 2022)
Renu Khanna is a trailblazer in participatory action researcher, particularly in womens health and human rights. In the early 80s, she began using PAR as part of her broader work with the Social Action for Rural and Tribal Inhabitants of India or SARTHI. Its overall purpose was to give women a meaningful voice in their own health care. She is one of the co-founders of the Society for Health Alternatives in Badadora India. SAHAJ created feminist-inspired maternal health programs. She's worked mobilizing traditionally marginalized groups in the tribal areas of Gujarat, the urban poor, and subsequently on health issues of sexual minorities, people living with disabilities, and adolescents. She has over 40 years of experience as a trainer, an action researcher, and evaluator, and a policy analyst in India. In this podcast, she talks about her journey through participatory training, participatory research and evaluation, and work with a feminist coalition developing innovative gender transformativ and evaluation.
Keywords: Women's Health and Human Rights